Barriers and Drivers of Green Supply Chain Management: a Case Study of Ukraine - Borys Kormych; Tetiana Averochkina; Olga Savych; Halyna Pivtorak (International Journal of Supply Chain Management, 2019)
Any change in a system requires a thorough preparation, especially when third parties are concerned. Introduction of green supply chain management (GSCM) is not an exemption. Various factors, like barriers and drivers, are able both to accelerate and inhibit the process of GSCM introduction. Thus, the importance of prior knowledge of such factors is difficult to underestimate. There has been a number of studies relates to barriers and drivers affecting GSCM introduction in various countries and industries. As soon as there were few GSCM-related researches in Ukraine, a country with powerful manufacturing and processing industries, this study is aimed to determine factors influencing GSCM introduction in manufacturing companies of the country.Based on results of filled-in and returned questionnaire distributed among 2000 Ukrainian manufacturing companies, 16 barriers and 22 drivers for GSCM introduction were identified. The statistical analysis showed that most important barriers are cost of implementation, lack of demand from customers, market competition, lack of government support and suppliers readiness to GSCM. Among most significant drivers are issues related to export, market and competitors, customers, costs reduction and financial benefits and liability and penalties imposed on environment legislation breaking entities.The results of this study can be applied both by scientists and environment / sustainability management professionals for further researches with the purpose of defining drivers and barriers and developing recommendations on GSCM introduction in certain country, industry or entity. Findings of the study together with further researches can be useful for governmental authorities for defining GSC-driving policies and regulations.